Chediak-Higashi syndrome in accelerated phase masquerading as severe acute malnutrition. (31st March 2014) - Karande, Sunil; Agarwal, Shruti; Gandhi, Bhaumik; Muranjan, Mamta
Abstract : A toddler presented with poor appetite, weight loss and frequent respiratory tract infections for the past 6 months, fever and increasing paleness for the past 2 months and bilateral pedal oedema for the past 1 month. Anthropometry confirmed severe acute malnutrition. Clinical and laboratory evaluation revealed that the child also had hypopigmented hair and skin, splenohepatomegaly, pancytopenia and hypoalbuminaemia. The coexistence of hypopigmentation and suspected low immunity prompted us to investigate the child's hair, peripheral blood smear and bone marrow. Hair under light microscopy showed evenly distributed, large melanin granules, suggestive of Chediak-Higashi syndrome (CHS). Peripheral blood smear and bone marrow aspirate examinations revealed abnormal large intracytoplasmic granules, which was diagnostic of CHS. The child's investigations revealed coexistent hemophagocytic lymphohistiocytosis, confirming the diagnosis of CHS in 'accelerated phase', which is fatal if not treated. The parents prematurely took the child home against medical advice, before definitive therapy could be instituted.